Pore-Forming Proteins as Mediators of Novel Epigenetic Mechanism of Epilepsy - Surguchov, Andrei; Surgucheva, Irina; Sharma, Mukut; Sharma, Ram; Singh, Vikas (Frontiers in Neurology, 2017)
Epilepsy is a disorder of the brain characterized by an enduring predisposition to generate epileptic seizures. In the last two decades, numerous gene defects underlying different forms of epilepsy have been identified with most of these genes encoding ion channel proteins. Despite these developments, the etiology of majority of non-familial epilepsies have no known associated genetic mutations and cannot be explained by defects in identified ion channels alone. We hypothesize that de novo formation of ion channels by naturally unfolded proteins (NUPs) increases neuronal excitability. Altered ionic homeostasis may initiate/contribute to cellular cascades related to epileptogenesis in susceptible individuals. Here we consider two small proteins, namely, alpha-synuclein and stefin B, as prototypical candidates to illustrate the underlying mechanism(s). Previous work points to an association between epilepsy and alpha-synuclein or stefin B, but the mechanism(s) underlying such association remains elusive. We review the evidence to link the structure-function of these proteins with disease processes. Epigenetic mechanisms unrelated to altered DNA sequence(s) that may affect epileptogenesis include transcriptional or post-transcriptional regulation. Such epigenetic mechanisms or their combination(s) enhance the levels of these proteins and as a result the ability to form annular structures, which upon incorporation into membrane form novel ion channels and disturb intracellular ion homeostasis. Alternative epigenetic mechanisms may change amyloidogenic proteins by post-translational modifications, increasing their propensity to form channels. Further research elucidating the details about the formation of ion channels through these mechanisms and their role in epileptogenesis may define new molecular targets and guide the development of new drug targets.